2018
DOI: 10.4103/jehp.jehp_29_17
|View full text |Cite|
|
Sign up to set email alerts
|

Utilizing mobile health method to emergency nurses' knowledge about Emergency Severity Index triage

Abstract: BACKGROUND:Mobile health has the potential to revolutionize the role of educators by empowering nurses to take more responsibility for their own learning. Hence, this study was designed to examine the effect of mobile health method to emergency nurses’ knowledge about Emergency Severity Index triage.MATERIALS AND METHODS:A two groups’ pool blind quasi-experimental study was performed on emergency department nurses working in hospitals affiliated with Isfahan University of Medical Sciences. The study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
(17 reference statements)
1
9
0
Order By: Relevance
“…(2018) also showed that the use of e-learning-based teaching methods has increased the level of nurses’ satisfaction with training related to emergency clinical care. [ 9 ] Therefore, it is important and necessary to pay attention to education and assessment of the level of awareness and performance of nursing students in stressful situations such as emergency departments. Moreover, student-based activities and the using new methods in educating and training nursing students have been important.…”
Section: Introductionmentioning
confidence: 99%
“…(2018) also showed that the use of e-learning-based teaching methods has increased the level of nurses’ satisfaction with training related to emergency clinical care. [ 9 ] Therefore, it is important and necessary to pay attention to education and assessment of the level of awareness and performance of nursing students in stressful situations such as emergency departments. Moreover, student-based activities and the using new methods in educating and training nursing students have been important.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies in Iran conducted to evaluate the effect of using mobile based education on the emergency nurses’ knowledge about the Emergency Severity Index,[ 15 ] determining the effect of e-learning education on primipar women's knowledge on neonatal care,[ 16 ] as well as evaluating the effect of distance learning through SMS on academic achievement and satisfaction of medical students. [ 17 ] Given the importance of reproductive health in young people and with regard to the previous studies, the researcher did not a study on the effect of education programs on promoting knowledge and self-care behaviors of students’ reproductive health based on smartphone-based software On the other hand, due to the innovation of the plan and the importance of software-based education on promoting healthy behaviors, the research team decided to conduct a study to investigate the effect of smartphone-based software on change of knowledge and self-care behaviors of reproductive health in married students as a susceptible population group in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile learning (m-learning) is a novel concept that has received a great deal of attention in educational societies as a pivotal point in the 21 st -century education. [ 1 2 ] There are several definitions for the term. Harden defines it as acquisition of learning using mobile technology (mobile phone, tablet, laptop, digital assistant, and the like).…”
Section: Introductionmentioning
confidence: 99%